Multiband planar monopole antenna using coupling control feed structure for mobile handsets. Issue 4 (April 2015) - Lee, Hongkoo; Lee, Jaesuk; Moon, Sungjin; Kim, Mingi; Kim, Hyeongdong
ABSTRACT In this article, a planar monopole antenna very close to the ground plane of mobile handsets is presented. Multiband operation is achieved by controlling the magnetic coupling between the feed structure and antenna structure with a slot structure and inductor. Measurements demonstrate that the proposed antenna possesses frequencies of 228 MHz (813–1041 MHz) and 601 MHz (1643–2244 MHz) with a voltage standing wave ratio of three even though the size of the proposed antenna is only 60 × 7 mm2. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:823–826, 2015